1978
DOI: 10.1152/jappl.1978.45.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory responses to intravenous and intrapulmonary CO2 in awake dogs

Abstract: Ventilatory responses to CO2 inhalation and CO2 infusion were compared in the awake dog. The CO2 was introduced directly into the systemic venous blood via a membrane gas exchanger in a femoral arteriovenous shunt circuit, and the extracorporeal blood flow, QX, was maintained constant at one of two rates: low, 0.5 l/min; or high, 2.0 l/min. A total of 13 experiments was performed in four dogs comprising 50 control and 25 inhalation and infusion observations at each of the two flow rates. Comparison of CO2-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…In several studies on anesthetized animals, it was claimed thatV E changed in proportion to the change in CO 2 delivery to maintain homeostasis of PaCO 2 (206,214,274,314,338). In contrast, in an equal number of studies, there was a change in PaCO 2 sufficient to account for the hyperpnea or hypopnea during CO 2 loading and unloading (39,118,138,171,209,277,284,300). Similar studies on awake sheep found that venous CO 2 loading that increased pulmonary CO 2 excretion up to 350% also increasedV E to the same extent as exercise induced increases in CO 2 excretion (275).…”
Section: Venous Co 2 Content As a Signal For The Exercise Hyperpneamentioning
confidence: 99%
“…In several studies on anesthetized animals, it was claimed thatV E changed in proportion to the change in CO 2 delivery to maintain homeostasis of PaCO 2 (206,214,274,314,338). In contrast, in an equal number of studies, there was a change in PaCO 2 sufficient to account for the hyperpnea or hypopnea during CO 2 loading and unloading (39,118,138,171,209,277,284,300). Similar studies on awake sheep found that venous CO 2 loading that increased pulmonary CO 2 excretion up to 350% also increasedV E to the same extent as exercise induced increases in CO 2 excretion (275).…”
Section: Venous Co 2 Content As a Signal For The Exercise Hyperpneamentioning
confidence: 99%
“…The demonstration of isocapnic hyperpnea in response to venous CO2 loading has been extrapolated to imply that the isocapnic hyperpnea of exercise may also be attributable solely to the associated increase in Vco2. However, an equally large number of other studies have been unable to demonstrate isocapnic hyperpnea in response to venous CO2 loading; and have therefore concluded that an increase in Vco2 alone cannot account for the isocapnic hyperpnea of exercise (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 98%
“…Experimental studies in animals have shown that changes in the venous blood 1 This work was supported by a grant from CNPq, Brazil. composition through C 0 2 remotion or infusion cause alterations in the pulmonary ventilation with no variation in the composition of the arterial blood [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%